RELEVANCE OF GAUDIYA VAISHNAVA PILGRIMAGE IN TODAY'S WORLD - Paul, Goutam Kumar; Londhe, Manali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the modern age of growing secularisation, disintegration of community, and psychological breakdown, the old spiritual practices are taking on new therapeutic and transformative applications. The following study focuses specifically on the contemporary context of Gaudiya Vaishnava pilgrimage, specifically the contemporary context of the Navadvipa Mandala Parikrama, which draws 50,000 followers every year worldwide. This study has found, through interviews and participant observation of this 16th-century spiritual practice, that there are three components for coping with contemporary challenges. These three components are: philosophical foundations based on the doctrine of Caitanya Mahaprabhu about the Acintya-Bheda-Abheda that transforms one’s geographic travel in the world into transcendental experience in every moment; mechanisms of cultural transformation which bring to life communities of inclusion across social classes and stratified society; and the therapeutic action of realising bodied bhava experiences which most participants express through our study as radical emotional transformation. The study also describes how the Gaudiya Vaishnava pilgrimage can develop to address contemporary needs, such as to combat the COVID-19 epidemic, to plleate the modern feelings of isolation, anxiety, and crisis of identity. Thus, one can view Gaudiya Vaishnava pilgrimage as a flexible spiritual paradigm addressing the philosophical, cultural, and psychological dilemmas of a secular world.